2012
DOI: 10.3390/ijms131216718
|View full text |Cite
|
Sign up to set email alerts
|

UVA Irradiation of Dysplastic Keratinocytes: Oxidative Damage versus Antioxidant Defense

Abstract: UVA affects epidermal cell physiology in a complex manner, but the harmful effects have been studied mainly in terms of DNA damage, mutagenesis and carcinogenesis. We investigated UVA effects on membrane integrity and antioxidant defense of dysplastic keratinocytes after one and two hours of irradiation, both immediately after exposure, and 24 h post-irradiation. To determine the UVA oxidative stress on cell membrane, lipid peroxidation was correlated with changes in fatty acid levels. Membrane permeability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…All antioxidants or the total antioxidant status (TAS) is often used to estimate the overall antioxidative status. Likewise, total oxidant status (TOS) is measured to determine a patient's overall oxidation state [30].…”
Section: Discussionmentioning
confidence: 99%
“…All antioxidants or the total antioxidant status (TAS) is often used to estimate the overall antioxidative status. Likewise, total oxidant status (TOS) is measured to determine a patient's overall oxidation state [30].…”
Section: Discussionmentioning
confidence: 99%
“…While UVA used to be considered as relatively innocuous, it now is emerging as a factor to mutagenesis 37 and damage to DNA, 38 proteins, and lipids, 39,40 thus associating it with cancer 41 and even dysregulation of immunity. 14 In ophthalmology, even though it is acceptable to use UVA for the treatment of keratoconus via collagen cross-linking, 42 studies have demonstrated that this technique becomes safer with the use of a protective ring around the limbal area to prevent damage to the stem cell compartment.…”
Section: Discussionmentioning
confidence: 99%
“…These cells are characterized by atypical nuclei and disorganized growth, leading to precancerous skin lesions [ 13 ]. Evidence demonstrates that UVA irradiation of dysplastic keratinocytes has detrimental effects in the first few hours of exposure, but long-term, it activates cell protection and survival mechanisms [ 14 ], aggravating their malignant potential. Additionally, malignancy was previously shown to be aggravated by alterations in cellular lipid metabolism [ 15 , 16 ] to favor cell survival and proliferation.…”
Section: Introductionmentioning
confidence: 99%